P3.007* Gonorrhoea, Syphilis, Chlamydia and Trichomonas in Children Under Thirteen Years of Age: National Surveillance in the UK and Republic of Ireland. (13th July 2013) - Rogstad, K E; Hughes, G; Debelle, G; Evans, J; Reading, R
Abstract : Background: Children who have been sexually abused (CSA) are potentially at risk of sexually transmitted infections (STI). It is not known how frequently such infections are identified within the population nor whether the implications of the mode of transmission are recognised and investigated appropriately. Methods: Active surveillance occurred through the British Paediatric Surveillance Unit system (www.rcpch.ac.uk/bpsu ) which covers all paediatricians (estimated > 95%) in UK and Republic of Ireland. Consultant paediatricians were asked to report cases with laboratory confirmed Neisseria gonorrhoeae (Ng), Treponema pallidum (Tp), Chlamydia trachomatis (Ct) or Trichomonas vaginalis (Tv) in children aged 1 to 12 years between January 2010 and January 2012. Anyone reporting a case was sent a clinical questionnaire. The adequacy of the initial and confirmatory diagnostic tests was judged against relevant national guidelines. Child protection investigations undertaken were arranged into a hierarchical classification. Results: Fifteen cases were reported - 7 Ng, 6 Ct, 1 Tp and 1 Tv. Fourteen presented because of symptoms (5 with ophthalmic symptoms), 3 had isolated ophthalmic infections), 1 following alleged CSA. Eleven of 15 had other indicators of possible CSA including allegation, behavioural or previous child protection concerns. Tests used were adequate and all had additional STI testing undertaken including 10 HIV and 12 Tp and hepatitis B. All but one case were referred for multi-agency child protection investigations, in three cases sexual CSA was confirmed at court or case conference (some outcomes awaited). Conclusion: This is the first population-based study of bacterial STI incidence in under 13 year-olds in the UK. Incidence was very low. Once detected, there are high levels of screening for other STIs using appropriate tests in line with national guidelines, and assessments for CSA. This is an improvement on a previous study on HSV1 and may be a result of better guidance and evidence base.